Breaking Away From the Male Stereotype of a Specialist: Gendered Language Affects Performance in a Thinking Task - Kollmayer, Marlene; Pfaffel, Andreas; Schober, Barbara; Brandt, Laura (Frontiers in Psychology, 2018)
This experimental online-survey study investigated if different written language forms in German have an effect on male bias in thinking. We used answers to the specialist riddle as an indicator for male bias in mental representations of expertise. The difficulty of this thinking task lies in the fact that a gender-unspecified specialist is often automatically assumed to be a man due to gender stereotypes. We expected that reading a text in gender-fair language before processing the specialist riddle helps readers achieve control over automatically activated gender stereotypes and thus facilitates the restructuring and reinterpretation of the problem, which is necessary to reach the conclusion that the specialist is a woman. We randomly assigned 517 native German speakers (68% women) to reading a text on expertise written either in gender-fair language or in masculine generics. Subsequently, participants were asked to solve the specialist riddle. The results show that reading a text in gender-fair language before processing the riddle led to higher rates of answers indicating that the specialist is a women compared to reading a text in masculine generics (44% vs. 33%) in women and men regardless of their self-stereotyping concerning agency and communion. The findings indicate that reading even a very short text in gender-fair language can help people break their gender-stereotype habit and thus reduce male bias in thinking. Our research emphasizes the importance of using gender-fair language in German-language texts for reducing gender stereotypes.